Distributed LQG control of a water delivery canal with feedforward from measured consumptions - Lemos, João (2012)
This work addresses the design of distributed LQG controllers for water delivery canals that include feedforward from local farmer water consumptions. The proposed architecture consists of a network of local control agents, each connected to one of the canal pools and sharing information with their neighbors in order to act in a coordinated way. In order to improve performance, the measurement of the outflows from each pool is used as a feedforward signal. Although the feedforward action is local. It propagates due to the coordinates procedure. The paper presents the distributed LQG algorithm with feedforward and experimental results in a large scale pilot water delivery canal.